Cardiovascular risk factor management of myocardial infarction patients with and without diabetes in the Netherlands between 2002 and 2006: a cross-sectional analysis of baseline data. Issue 6 (31st October 2012) - Soedamah-Muthu, Sabita S; Geleijnse, Johanna M; Giltay, Erik J; Kromhout, Daan
Abstract : Objective: We examined levels and trends in cardiovascular risk factors and drug treatment in myocardial infarction (MI) patients with and without diabetes. Design: Cross-sectional analysis of baseline Alpha Omega Trial data, a randomised controlled trial. Setting: 32 hospitals in the Netherlands. Participants: In total, we had 1014 MI patients with diabetes (74% men) and 3823 without diabetes (79% men) aged 60–80 years, analysed over the period 2002–2006. Results: Between 2002 and 2006, a significantly decreasing trend in the prevalence of obesity (−5%, ptrend =0.02) and in systolic blood pressure (BP) levels (−5 mm Hg, ptrend <0.0001) was demonstrated in non-diabetic patients, but not in diabetic patients. In 2006, obesity, mean systolic BP and serum triglyceride levels were significantly higher, whereas high-density lipoprotein cholesterol levels were lower in diabetic patients compared to those without. Prescription of antihypertensive drug (diabetic vs non-diabetic patients respectively, 95% vs 93%, p=0.08) and statin treatment were high (86% and 90%, p=0.11). Conclusions: A high proportion of MI patients with and without diabetes was similarly treated with cardiovascular drugs. In spite of high drug treatment levels, more adverse risk factors were found in patients with diabetes.